Factors regulating viable cell density in the intervertebral disc: blood supply in relation to disc height. - Boubriak, O; Watson, N; Sivan, S; Stubbens, N; Urban, J (2013)
The intervertebral disc is an avascular tissue, maintained by a small population of cells that obtain nutrients mainly by diffusion from capillaries at the disc-vertebral body interface. Loss of this nutrient supply is thought to lead to disc degeneration, but how nutrient supply influences viable cell density is unclear. We investigated two factors that influence nutrient delivery to disc cells and hence cell viability: disc height and blood supply. We used bovine caudal discs as our model as these show a gradation in disc height. We found that although disc height varied twofold from the largest to the smallest disc studied, it had no significant effect on cell density, unlike the situation found in articular cartilage. The density of blood vessels supplying the discs was markedly greater for the largest disc than the smallest disc, as was the density of pores allowing capillary penetration through the bony endplate. Results indicate that changes in blood vessels in the vertebral bodies supplying the disc, as well as changes in endplate architecture appear to influence density of cells in intervertebral discs.